Evaluating the Benefits of Electronic Commerce in Small and Medium Enterprises - Marshall, Peter; McKay, Judy (Australasian Journal of Information Systems, 2002)
This paper outlines and analyses the behaviours of small and medium enterprises with respect to the evaluation of electronic commerce investments, and the subsequent realisation of the anticipated benefits from those investments. The responses of executives who participated in the study suggested that on-going involvement in electronic commerce did not come cheaply. Nonetheless, our study suggests that there were generally ad hoc approaches to evaluation of the proposed electronic commerce investments, almost non-existent post-implementation reviews, few measures of success, and generally speaking, there was little evidence of there being proactive management of the realisation of benefits of those investments. Perhaps not surprisingly, the group interviewed seemed somewhat disappointed with the outcomes of their electronic commerce initiatives. The implications of these findings are discussed, particularly for countries where small and medium enterprises contribute a large proportion of total economic activity, and where thus it is vital for small and medium enterprises to successfully engage in electronic commerce if the country is to derive the benefits of the new economy.